Functional profiles of soil microbial communities in the alpine and temperate grasslands of China. Issue 1 (30th April 2022) - Yang, Yunfeng; Zhou, Jizhong; Guo, Xue
Abstract: Grassland ecosystems in cold regions are typical of short growing seasons and limited primary productivity, rendering soil microorganisms as major ecosystem engineers in governing biogeochemical cycling. Climate warming and extensive livestock grazing have dramatically influenced soil microbial diversity and function in grassland worldwide, but it remains elusive how functional microbial communities exist and respond to global changes. Here, we present a review to highlight similarities and differences in soil functional microbial communities between alpine grasslands in the Qinghai‐Tibet Plateau and temperate grasslands in the Inner Mongolian Plateau, both of which are major plateaus in China, but differ substantially in geography. We show that many specialized functional groups thrive under harsh conditions, exhibiting a high functional diversity. Their community compositions mirror the heterogeneity and complexity of grassland soils. Moreover, functional microbial responses to environmental changes have been extremely variable, with few consistent patterns across both plateaus. Because we identify a lack of technical standardization that prevents in‐depth comparative studies for functional microbial communities, we conclude the review by outlining several research gaps that need to be filled in future studies. Abstract : Responses of soil functional microorganisms of alpine and temperate grasslands to environmental perturbation differ substantially, mirroring the heterogeneity and complexity of grassland soils.